Unexpected Inflammation in the Sympathetic Ganglia in Thromboangiitis Obliterans - Farzadnia, Mahdi; Ravari, Hassan; Masoudian, Mitra; Valizadeh, Narges; Fazeli, Bahare (International Journal of Angiology, 2017)
The aim of this study was to inspect more closely the microscopic and molecular sympathetic ganglia histology in thromboangiitis obliterans (TAO). The paraffin block and frozen RNAlater-treated tissue of the lumbar sympathetic ganglia of 19 TAO Caucasian male patients were evaluated. The gene expression of cluster of differentiation 4 (CD4) and cluster of differentiation 8 (CD8) markers in the frozen RNAlater-treated sympathetic ganglia tissues were evaluated by real-time polymerase chain reaction. Unexpectedly, lymphocyte infiltration was observed in all of the histological sections, ranging from scattered to moderate lymphocyte infiltration. In seven patients, five of them underwent below-knee amputation, neutrophil infiltration was observed in addition to lymphocyte infiltration. The gene expression of the CD8 marker in all of the samples with the expression of CD4 markers in only four tissue samples was demonstrated. The expression of CD8 in comparison to CD4 was approximately 4.37-fold changes using Pfaffle method. It appears that inflammation of the sympathetic ganglia plays a role in the pathophysiology of TAO and its outcome. Sympathetic ganglia inflammation may be responsible for general vasoconstriction, vascular inflammation, and the increased risk of thrombotic events, by activating the platelets. The dominant infiltration of T cytotoxic lymphocytes and neutrophils in sympathetic ganglia may probably support the idea of possible intracellular infectious pathogen trigger for TAO and consequently infiltration of pathogen-specific T cells into the sympathetic ganglia in TAO.
Keywords: thromboangiitis obliterans; Buerger's disease; sympathetic ganglia; inflammation; sympathectomy